2004
DOI: 10.1161/01.cir.0000127448.25065.6e
|View full text |Cite
|
Sign up to set email alerts
|

A Chicken in Every Pot and a Drug-Eluting Stent in Every Lesion

Abstract: A 78-year-old man is admitted with episodes of severe angina associated with hypotension. Urgent angiography finds critical left main stenosis with wellpreserved left ventricular function (Figure 1). While discussing the treatment plan with the physician, the patient suddenly manifests sustained ventricular fibrillation. Prompt electrocardioversion restores sinus rhythm, but there is electromechanical dissociation and no blood pressure. Chest compressions are initiated. A guiding catheter quickly inserted into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In coronary arteries, restenosis inhibition by drug-eluting stents is safe and efficacious (3). Nevertheless, in some procedures, such as treatment of instent restenosis or stenoses in bifurcations, stents are either not desirable or not applicable (23). A clinical trial of coronary in-stent restenosis has shown effectiveness of paclitaxel-coated balloons (24).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In coronary arteries, restenosis inhibition by drug-eluting stents is safe and efficacious (3). Nevertheless, in some procedures, such as treatment of instent restenosis or stenoses in bifurcations, stents are either not desirable or not applicable (23). A clinical trial of coronary in-stent restenosis has shown effectiveness of paclitaxel-coated balloons (24).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Animal experiments 1,2 and clinical trials 3 indicated that sustained release and the choice of a suitable drug were mandatory for effective inhibition of restenosis during the months and years after angioplasty. 4,5 It is surprising that a single immediately released dose of a drug requiring sustained release when coated on a stent inhibits neointimal proliferation in animals for weeks and restenosis in patients for years. 6 Paclitaxel concentrations in the vessel wall shortly after treatment with the dissolved drug or drug-coated balloons have been reported [7][8][9][10][11][12][13] but little is known about the residence time of the drug, which may be relevant for the persistent effect if administered only during the short time of balloon inflation.…”
mentioning
confidence: 99%
“…This prompted a 'PCI frenzy' and 'DES euphoria', with calls to "put surgeons out of business" (1). Cardiac surgeons went from denial to despair and, in many instances, panic.…”
Section: La Vie Et Les Difficultés D'un Chirurgien Cardiaquementioning
confidence: 99%